2023
DOI: 10.1002/art.42460
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Photosensitivity by the Hippo Pathway in Lupus Skin

Abstract: Objective. Photosensitivity is one of the most common manifestations of systemic lupus erythematosus (SLE), yet its pathogenesis is not well understood. The normal-appearing epidermis of patients with SLE exhibits increased ultraviolet B (UVB)-driven cell death that persists in cell culture. Here, we investigated the role of epigenetic modification and Hippo signaling in enhanced UVB-induced apoptosis seen in SLE keratinocytes.Methods. We analyzed DNA methylation in cultured keratinocytes from SLE patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…When people with SLE are exposed to UVR, the pathogenic stimulus travels from the skin to the draining lymph nodes through lymphatic vessels and 27 It has been shown that keratinocyte apoptosis caused by altered methylation of Hippo Pathway is correlated with skin photosensitivity in SLE. 28 On the other hand, increased interferon Kappa in keratinocytes improves its sensitivity to UVR exposure and aggravates disease. 29 UVR can induce the type I IFN response to cause the secretion of Th1 associated chemokines such as C-X-C motif chemokine ligand 9/10 in T cells, which contributes to the further recruitment of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…When people with SLE are exposed to UVR, the pathogenic stimulus travels from the skin to the draining lymph nodes through lymphatic vessels and 27 It has been shown that keratinocyte apoptosis caused by altered methylation of Hippo Pathway is correlated with skin photosensitivity in SLE. 28 On the other hand, increased interferon Kappa in keratinocytes improves its sensitivity to UVR exposure and aggravates disease. 29 UVR can induce the type I IFN response to cause the secretion of Th1 associated chemokines such as C-X-C motif chemokine ligand 9/10 in T cells, which contributes to the further recruitment of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…SLE patients and healthy controls ( Table S1 ) were recruited from the Taubman Institute Innovative Research Program Personalized Medicine through Integration of Immune Phenotypes in Autoimmune Skin Disease (TIIP-PerMIPA cohort) as described in a previous study. 50 As per the principles of the Declaration of Helsinki, all patients and healthy controls gave written, informed consent before inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%